Exploration Of Service Strategy and Operational Innovation In Service SME’s In Purworejo Regency - Hubi Rahmat Andika; Ishak Ishak; Murry Harmawan Saputra; Tika Awalia (At-Tadbir : jurnal ilmiah manajemen, 2026)
This study aims to analyze the integration of digital service strategies and operational innovation in service MSMEs in Purworejo Regency. The study used a descriptive qualitative approach with a multiple case study design on ten service MSMEs. Data were collected through interviews and observations, then analyzed using the Miles & Huberman interactive analysis model, which includes data condensation, data presentation, and conclusion drawing. Data processing in this study used Nvivo software version 12. The results show that customer orientation is at the core of the implementation of digital strategies and operational innovation. Digital strategies such as the use of social media, optimization of Google Maps, and paid promotions act as external triggers to expand market reach and increase customer interaction. Meanwhile, operational innovations such as pre-order systems, payment flexibility, application use, and increased work efficiency serve as internal adjustments to maintain service quality and responsiveness. This study concludes that digital strategies and operational innovation must be carried out in tandem to increase the competitiveness of service MSMEs. These findings emphasize that digital strategy transformation depends not only on the use of technology but also on the readiness of simultaneous internal process innovation